SP 10. Innsbruck experience in neuropathic pain syndromes: Re-think and re-construct old methods for better results. Issue 9 (September 2016) - Eisner, W.; Sohm, F.; Rehwald, R.; Scharnboeck, L.; Siedentopf, C.; Quirbach, S.; Gizewski, E.; Kerschbaumer, J.
Abstract : Introduction: In the last 25 years neuromodulation by deep brain stimulation gained widely acceptance starting in the field of movement disorders and getting further indications in pain syndroms and mood disorders. Surgical interventions should only be considered being a treatment option after proving ineffectiveness of conservative therapy forms. The highly acclaimed success of deep brain stimulation in Parkinsons disease, essential tremor, dystonia, chorea huntington, tourette syndrome, cannot be translated 1:1 to neuropathic pain syndromes. The EFNS guidelines on neurostimulation therapy for neuropathic pain published in the European Journal of Neurology 2007; 14: 952–970 revealed DBS against pain to be less effective than in movement disorders. The publication identified several reviews and one meta-analysis, which conclude that DBS is more effective for nociceptive pain than for neuropathic pain (63% vs. 47% long-term success). In patients with neuropathic pain, moderately higher rates of success were seen in patients with peripheral lesions. Because neuropathic pain syndromes are a complex compilation of missing information in different pathways to and within the brain resulting in the different aspects of pain consisting of sensation, perception, mood, emotion and vegetative aspects. Material and methods: We will demonstrate different neuropathic pain syndromes following neurosurgical stereotactic interventions for neuromodulation. We were able to enhance the reduced input to the consciousness of man and women by modulation of the two main input areas namely the sensory thalamus and the posterior limp of the internal capsule. We modified the implantation site in the internal capsule because of ineffectiveness of the historical target and an anatomical chaos in the literature on the anatomical construction of the posterior limp of the internal capsule. By doing so we are able to cover all essential afferent fibers to the sensori-motor and the parietal cortex. In comparison to all other methods or other implantation centers a minimum of 2 stimulation electrodes have to be implanted per cerebral hemisphere. 30 patients were treated by neuromodulation against neuropathic pain syndromes. Without motor cortex stimulation and deep brain stimulation against cluster headache we operated 18 patients against neuropathic pain syndromes with our two electrode method. 6 trigeminal neuropathia (5 analgesia dolorosa) patients, 4 peripheral nerve injury patients and 8 post stroke patients. Results: All patients had at least 60% up to 100% pain reduction. Some patients developed a decrease of the stimulation effect by "overstimulation". Intermittent stimulation and our method of intensity modulation is able to reduce habituation of stimulation effects. The anterior cingulate gyrus stimulation according to T. Aziz will complete the armentarium of deep brain stimulation against neuropathic pain syndromes. Prospective randomized double blind studies in neuromodulation against neuropathic pain are still missing and will be conducted in the near future.